Tinjauan Yuridis Tindak Pidana Muatan Perjudian Terhadap Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Ary Hendri Saputra; Ernu Widodo; Vallencia Nadya Paramita (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
A good human being always uses the time given to him by the creator to be used to create useful works. One of the acts that is useless and has been in the habit in the past until now is gambling. Legal issues of this normative legal research: How does gambling crime occur in society? What is meant by the phrase gambling content as referred to in Law Number 11 of 2008 concerning Information and Electronic Transactions? Gambling crimes in society are a complex and growing problem. The crime of gambling is regulated in Articles 303 and 303 bis of the Criminal Code, which states that gambling is any game that contains elements of betting in the hope of getting a profit based on luck or skill. Gambling encompasses a wide range of forms, from traditional games such as cockfighting and lotteries to online gambling. This activity not only involves people from the lower layers, but also reaches the middle and upper classes. Article 27 paragraph (2) of Law No. 11 of 2008 Electronic Information and Transactions The phrase gambling content includes the following elements: 1. Intentional, An act is carried out with the intention to distribute or transmit gambling content. 2. Without Rights, the Perpetrator does not have permission or the right to perform such acts. 3. Gambling Content, Content distributed or transmitted contains elements of gambling, either directly or indirectly.